Penggunaan Aplikasi Microsoft Mathematics untuk Pengembangan Bahan Ajar matematika Siswa - Rizki, Fitria; Widyastuti, Rany (Desimal: Jurnal Matematika, 2019)
This study aims to develop mathematics teaching materials assisted by Microsoft Mathematics applications in class XI students. The research and development method used is the 4D model proposed by Thiagarajan which consists of 4 stages: (1) define; (2) design; (3) develop and (4) disseminate. Researchers used qualitative and quantitative data analysis techniques. This study uses data collection techniques namely questionnaire (questionnaire) in the form of a Likert scale for students responses. The results of the study are media in the form of mathematics teaching materials assisted by Microsoft Mathematics applications that are suitable to be used as learning media to improve student learning motivation. The feasibility of learning media produced from material experts and media experts is valid and is suitable for use as a learning medium. The response of students to the learning media obtained in the small group test is very interesting with an average score of 83%. In field testing, the criteria for attractiveness are very interesting with an average score of 87%.